Halal Industry Development in the Fashion Goods Sector in Indonesia - Ika Choilia Indrianti Cholifah (Universitas Negeri Surabaya, 2026)
The halal industry has shown consistent growth over the past decade and has become a key pillar of the global economy, extending beyond the food sector to consumer goods such as fashion. This study examines the development of the halal fashion industry and Indonesia’s strategic role in advancing this sector. Using a literature review approach, the research synthesizes academic studies, industry reports, and recent publications on halal fashion. The findings indicate that Indonesia has strong potential to develop its halal fashion industry and position itself as a global reference, as reflected in its leading ranking in the State of the Global Islamic Economy Report (2024) through the Indonesia Global Halal Fashion (IGHF) initiative. The development of this industry is supported by the integration of conducive industrial policies, effective halal branding, sharia-based innovation, and improved consumer literacy and behavior. Strengthening these elements is essential for building a competitive and sustainable halal fashion industry ecosystem. Overall, the study underscores that the integration of religious values, creativity, and modern economic practices is fundamental to the long-term global competitiveness of Indonesia’s halal fashion industry.